Phenome-wide screening of the putative causal determinants of bipolar affective disorder using genetic data - Bin Hu; Qi Zhou; Hao Wu; Dejiang Yang; Chongyu Xiong; Xiaowei Zhang (PLoS ONE, 2026)
Bipolar affective disorder (BPAD) is a chronic psychiatric condition with high heritability (60–85%) and significant phenotypic variability, complicating its etiological understanding. Genome-wide association studies (GWAS) have revealed genetic overlaps with diverse traits, suggesting pleiotropy. This study aimed to identify shared genetic factors and infer causal relationships using large-scale GWAS data.BPAD GWAS summary statistics were obtained from the UK Biobank via the Complex Trait Genetics Virtual Lab (CTG-VL) platform. Genetic correlations with 1,504 traits were estimated using linkage disequilibrium score regression (LDSC), with quality filters ensuring heritability (h² > 0.05, p < 0.05). The latent causal variable (LCV) model was applied to assess genetic causal proportion (GCP), distinguishing vertical from horizontal pleiotropy. Multiple testing was corrected using false discovery rate (FDR < 5%).Seventy-five traits showed significant genetic correlations with BPAD (FDR < 5%). Among these, 47 exhibited strong causal associations (|GCP| > 0.6; FDR < 5%), and 28 showed partial genetic causality (|GCP| < 0.6; FDR < 5%). Our results showed that the genetic variants affecting BPAD risk had positive and negative effects on other complex phenotypes. For example, we found that genetic predisposition to BPAD increased the risk of depression, excessive worry, and altered blood levels of vitamin C and calcium. On the other hand, we found that genetic variants influencing the use of certain supplements and medications, such as glucosamine/chondroitin, multivitamin mineral preparations, vitamin D, clopidogrel, and nicorandil, as well as the exposure to gas or solid fuel cooking/heating, decreased BPAD risk. Additionally, we detected that genetic variants affecting some mental, work, living, dietary, and physical health factors also increased BPAD risk. Our study provides novel insights into the potential causal determinants of BPAD and suggests new avenues for future research to elucidate the biological mechanisms and pathways involved in this disorder.